2017
DOI: 10.1111/bph.14075
|View full text |Cite
|
Sign up to set email alerts
|

Update on the pharmacology of calcitonin/CGRP family of peptides: IUPHAR Review 25

Abstract: The calcitonin/CGRP family of peptides includes calcitonin, α and β CGRP, amylin, adrenomedullin (AM) and adrenomedullin 2/intermedin (AM2/IMD). Their receptors consist of one of two GPCRs, the calcitonin receptor (CTR) or the calcitonin receptor-like receptor (CLR). Further diversity arises from heterodimerization of these GPCRs with one of three receptor activity-modifying proteins (RAMPs). This gives the CGRP receptor (CLR/RAMP1), the AM and AM receptors (CLR/RAMP2 or RAMP3) and the AMY AMY and AMY receptor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
483
1
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 291 publications
(506 citation statements)
references
References 113 publications
16
483
1
6
Order By: Relevance
“…We hypothesized that the release of stored calcium by ryanodine may selectively stimulate the exocytosis of CGRP‐containing LDCVs, which will be followed by the increase in MEPP amplitude as the result of activation of CGRP receptors by released endogenous CGRP. To test this hypothesis, we studied the action of 0.1 μM of ryanodine in the presence of truncated CGRP (CGRP 8‐37 , 1 μM) which is widely used as CGRP‐receptor blocker (Gaydukov et al., 2016; Han, Adwanikar, Li, Ji, & Neugebauer, 2010; Hay, Garelja, Poyner, & Walker, 2017; Wu et al., 2015). We have shown that CGRP 8‐37 alone had no significant effect on MEPP amplitude (Gaydukov et al., 2016).…”
Section: Resultsmentioning
confidence: 99%
“…We hypothesized that the release of stored calcium by ryanodine may selectively stimulate the exocytosis of CGRP‐containing LDCVs, which will be followed by the increase in MEPP amplitude as the result of activation of CGRP receptors by released endogenous CGRP. To test this hypothesis, we studied the action of 0.1 μM of ryanodine in the presence of truncated CGRP (CGRP 8‐37 , 1 μM) which is widely used as CGRP‐receptor blocker (Gaydukov et al., 2016; Han, Adwanikar, Li, Ji, & Neugebauer, 2010; Hay, Garelja, Poyner, & Walker, 2017; Wu et al., 2015). We have shown that CGRP 8‐37 alone had no significant effect on MEPP amplitude (Gaydukov et al., 2016).…”
Section: Resultsmentioning
confidence: 99%
“…Table and Figure summarize the composition, agonist, and antagonist pharmacology of the calcitonin family of receptors . It is noteworthy that CGRP is a potent agonist at the CGRP receptor that is made up of CLR with RAMP1, and also the AMY1 receptor that is made up of CTR with RAMP1 . The converse is not, however, true, as amylin is only a weak activator of the CGRP receptor …”
Section: Introductionmentioning
confidence: 99%
“…In this model, the C‐terminal region of CGRP first binds with high affinity to the extracellular N‐terminal regions of CLR and RAMP1 forming an affinity trap that increases the local concentrations of CGRP to allow the N‐terminal of CGRP to interact with the juxta‐membrane region of CLR and trigger the accumulation of cAMP. The binding of CGRP to the AMY1 receptor (CTR + RAMP1) is thought to be a similar affinity trap mechanism due to the contribution of a common set of amino acids shared between CLR and CTR together with a common interaction with RAMP1 residue tryptophan 84 …”
Section: Introductionmentioning
confidence: 99%
“…CGRP may exert its effects through several different receptors, including the CGRP receptor, the calcitonin receptor, amylin receptors, and adrenomedullin receptors . The receptors that bind CGRP‐related neuropeptides may show some structural similarities (Table ) .…”
Section: Overview Of Cgrp Receptor Structure and Signal Transductionmentioning
confidence: 99%
“…Notably, two receptors are known to bind CGRP with high affinity – the CGRP receptor and the amylin receptor AMY1 . These receptors are part of the calcitonin receptor family, which includes other receptors that can also bind CGRP, albeit with lower affinities …”
Section: Overview Of Cgrp Receptor Structure and Signal Transductionmentioning
confidence: 99%